Social Media Marketing :Instagram, Whatsapp, Dan Web Mampukah Mempengaruhi Keputusan Pembelian - Hermani, Sofiati; Nisa, Qutsi Khoiru Janahtul; Linawati, Linawati (Jurnal Ekonomi Bisnis Manajemen Prima, 2023)
The purpose of this study was to determine the effect of the social media marketing Instagram, whatshapp, and the Web on purchasing decisions. This research is quantitative in nature with the amount of data collected as many as 100 respondents. The research method used is data using multiple linear regression analysis, namely by collecting data from data sources, namely primary data, namely questionnaires and secondary data, this is to determine the effect of the independent variable on the dependent variable. The results of the analysis prove that there is a positive and significant influence of Instagram, Whatsapp and Web social media marketing both partially and simultaneously on purchasing decisions at Swasana by Temata Restaurant. Among the three social media that most dominantly influence purchasing decisions is the Web social media.